Two generalizations of Lucas sequence - Goksal, Bilgici (Elsevier BV, 2014)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: generating function; Fibonacci and Lucas numbers and polynomials and generalizations; generalized Lucas sequence; generalized Fibonacci sequence; Binet formula; 16. Peace & justice